Agrometeorological models for estimating sweet cassava yield - Moreto, Victor Brunini; Aparecido, Lucas Eduardo De Oliveira; Rolim, Glauco De Souza; Moraes, José Reinaldo Da Silva Cabral De (Escola de Agronomia/UFG, 2018)
ABSTRACT Brazil is the fourth largest producer of cassava in the world, with climate conditions being the main factor regulating its production. This study aimed to develop agrometeorological models to estimate the sweet cassava yield for the São Paulo state, as well as to identify which climatic variables have more influence on yield. The models were built with multiple linear regression and classified by the following statistical indexes: lower mean absolute percentage error, higher adjusted determination coefficient and significance (p-value < 0.05). It was observed that the mean air temperature has a great influence on the sweet cassava yield during the whole cycle for all regions in the state. Water deficit and soil water storage were the most influential variables at the beginning and final stages. The models accuracy ranged in 3.11 %, 6.40 %, 6.77 % and 7.15 %, respectively for Registro, Mogi Mirim, Assis and Jaboticabal.

RESUMO O Brasil é o quarto maior produtor mundial de mandioca, tendo as condições climáticas como principais fatores na regulação de sua produção. Objetivou-se desenvolver modelos agrometeorológicos para estimar a produtividade de mandioca doce para o estado de São Paulo, bem como identificar quais variáveis ​​climáticas exercem maior influência sobre a produtividade. Os modelos foram construídos com regressão linear múltipla e classificados pelos seguintes índices estatísticos: menor erro percentual absoluto médio, maior coeficiente de determinação ajustado e significância (p-valor < 0.05). Identificou-se que a temperatura média do ar tem grande influência no rendimento da mandioca durante todo o ciclo, para todas as regiões do estado. O déficit hídrico e o armazenamento de água no solo foram as variáveis ​​mais influentes nos estágios inicial e final. A precisão dos modelos variou em 3,11 %, 6,40 %, 6,77 % e 7,15 %, respectivamente para Registro, Mogi Mirim, Assis e Jaboticabal.
Modelos agrometeorológicos para estimar o rendimento de mandioca doce
Keywords: Manihot esculenta; crop modeling; climatology; Manihot esculenta; modelagem de culturas; climatologia